On Anachronism. - Tambling, Jeremy (Manchester University Press, 2010)
*On Anachronism* joins together Shakespeare and Proust as the great writers of love to show that love is always anachronistic, and never more so when it is homosexual. Drawing on Nietzsche, Freud, Heidegger, Derrida, Blanchot and Levinas and Deleuze, difficult but essential theorists of the subject of?being and time? and?time and the other? the book examines why speculation on time has become so crucial within modernity. Through the related term?anachorism?, it considers how discussion of time always turns into discussion of space, and how this, too, can never be quite defined. It speculate.